Сервер управління науковим і навчальним експериментом - Гаврішев, В. Р.; Карнаушенко, В. П. (ХНУРЕ, 2019)
Today‘s scientific and education experiment usually based on computing technique. To create simple and clear real experiment server is the most demand problem in computerized instrumentation. This server must to have flexibility structure that supports various hardware. This work describes one of possible ways how to implement those requirements to PC based instrumentation.
Keywords: Сервер управління; науковий експиремент